A new cuttlefish, Sepia filibrachia n. sp., from the South China Sea with a redescription of Sepia mestus Gray, 1849 (Cephalopoda: Sepiidae) from eastern Australia - Reid, Amanda L.; Lu, Chung-Cheng (Zootaxa, 2005)
Based on two beachwashed cuttlebones, Sepia mestus Gray, 1849 was described in a single sentence. The whole animal remained largely unknown until partial descriptions were published by Adam and Rees (1966) and Lu (1998). Though well known by scuba divers as the ‘Common Sydney Cuttlefish’, or the ‘Red Cuttle’, the lack of an adequate description in the scientific literature has made identification and comparison with other species difficult. The discovery of some supposed S. mestus in the South China Sea (Khromov 1987) prompted the redescription of S. mestus. Khromov’s specimens, in addition to some more of the same species from Taiwan, were found to belong to a new species that is described here as S. filibrachia n. sp. It appears that S. mestus is most likely an eastern Australian endemic.